Role of dexmedetomidine as adjuvant in postoperative sciatic popliteal and adductor canal analgesia in trauma patients: a randomized controlled trial - Ahuja, Vanita (Korean J Pain, 2020)
BACKGROUND: The effect of dexmedetomidine as an adjuvant in the adductor canal block (ACB) and sciatic popliteal block (SPB) on the postoperative tramadol-sparing effect following spinal anesthesia has not been evaluated. METHODS: In this randomized, placebo-controlled study, ninety patients undergoing below knee trauma surgery were randomized to either the control group, using ropivacaine in the ACB + SPB; the block Dex group, using dexmedetomidine + ropivacaine in the ACB + SPB; or the systemic Dex group, using ropivacaine in the ACB + SPB + intravenous dexmedetomidine. The primary outcome was a comparison of postoperative cumulative tramadol patient-controlled analgesia (PCA) consumption at 48 hours. Secondary outcomes included time to first PCA bolus, pain score, neurological assessment, sedation score, and adverse effects at 0, 5, 10, 15, and 60 minutes, as well as 4, 6, 12, 18, 24, 30, 36, 42, and 48 hours after the block. RESULTS: The mean ± standard deviation of cumulative tramadol consumption at 48 hours was 64.83 ± 51.17 mg in the control group and 41.33 ± 38.57 mg in the block Dex group (P = 0.008), using Mann–Whitney U-test. Time to first tramadol PCA bolus was earlier in the control group versus the block Dex group (P = 0.04). Other secondary outcomes were comparable. CONCLUSIONS: Postoperative tramadol consumption was reduced at 48 hours in patients receiving perineural or systemic dexmedetomidine with ACB and SPB in below knee trauma surgery.